Policy messes and their management - Roe, Emery (Policy Sciences, 2016)
This paper presents a framework for better managing policy messes and draws implications for bad and good mess management in policy analysis and management. The framework has three foci: (1) the cognitive space in which policy messes develop, particularly in terms of gaps between macro-designers and micro-operators; (2) the unique domain of compete nce within that space where professionals manage the resulting messes by virtue of their skills in recognizing system-wide patterns, formula ting locally specific contingency scenarios and translating both patte rns and scenarios in highly reliable services; and (3) the ability of those mess and reliability professionals to be reliable in their domai n and with these skills by maneuvering across different performance mo des as conditions dictate—just-in-case, just-on-time, just-for-now or just-this-way.